Impact of Foot Width on Patient-Reported Outcomes Assessed by 3-Dimensional Foot Morphometry in Hallux Valgus - Ahn, Jungtae; Nam, Dae-Cheol; Jung, Gu-Hee (Clinics in orthopedic surgery, 2025)
Background: Patients with hallux valgus (HV) deformity often experience shoe-wearing discomfort, and increased foot width is considered a contributing factor. We assessed foot width using standing radiographs and 3-dimensional (3D) scans. This study aims to evaluate how these measurements are related to clinical outcomes in HV patients. Methods: This cross-sectional study enrolled 19 consecutive adults presenting for hallux valgus evaluation. All participants underwent weight-bearing radiographs and 3D structured-light scanning, followed by completion of patient-reported outcome measures including pain visual analog scale, EuroQol 5-Dimension 5-Level (EQ-5D-5L), and Manchester-Oxford Foot Questionnaire (MOXFQ). Radiographic measurements included intermetatarsal angle, hallux valgus angle, bone width, and soft tissue width. 3D parameters included maximal and horizontal forefoot width, ball circumference, instep circumference, and ball-to-instep ratio. Pearson correlations and multivariable regression analyses examined relationships between morphological parameters and patient-reported outcomes. Results: The cohort consisted of 14 women and 5 men with a median age of 57.0 years. Strong correlations were observed between radiographic and 3D measurements of bone and soft-tissue width (r = 0.93–0.97). The intermetatarsal angle showed moderate correlations with all 3D foot-width parameters (r = 0.54–0.65), while hallux valgus and interphalangeal angles did not demonstrate meaningful associations. In multivariable analyses, bone width was the predictor of MOXFQ-index scores and served as the predictor of social interaction difficulties. No dimensional parameters correlated with EQ-5D-5L scores. Domain-specific analysis revealed that bone width predicted social interaction problems, while maximal and horizontal width predicted walking/standing difficulties. Conclusions: In hallux valgus patients, both radiographic bone width and 3D-scan-derived ball-to-instep ratio show notable associations with social interaction difficulties on the MOXFQ, highlighting the role of forefoot width in shoe wearing discomfort and patient-reported outcomes. Integrating these measurements into clinical evaluation may inform personalized footwear selection and design, such as wider toe boxes or customized last shapes, to alleviate symptoms and improve functional and social outcomes for patients with hallux valgus. KCI Citation Count: 0